Improved path imbalance measurement of a fiber-optic interferometer based on frequency scanning interferometry. (17th July 2017) - Hou, C B; Wang, J G; Yang, J; Li, H Y; Yuan, Y G; Peng, F; Yuan, L B
Abstract: We developed a path imbalance measuring system using a reference interferometer with alterable optical path difference (OPD), aiming to eliminate the uncertainties due to synthetic wavelength measurement and remove the requirement of a known and stable reference OPD in frequency scanning interferometry. The path imbalance can be solved by using the phase ratios between the two interferometers produced before and after altering the OPD in the reference interferometer. The results have shown that the measurement uncertainty and the path imbalance are linearly related and a combined relative uncertainty of 4.9 × 10 −6 (1 σ ) in path imbalance measurement over a range from 0.5 m to 50 m is achieved. Besides, we analyzed the contributions to the uncertainty that limit the performance of the system, and we discussed how to obtain a better measurement uncertainty.